DIPG-03. TARGETING PI3K USING THE BLOOD BRAIN BARRIER PENETRABLE INHIBITOR, GDC-0084, FOR THE TREATMENT OF DIFFUSE INTRINSIC PONTINE GLIOMA (DIPG). (23rd April 2019) - Duchatel, Ryan; Jackson, Evangeline; Patabendige, Adjanie; Cain, Jason; Tsoli, Maria; Monje, Michelle; Alvaro, Frank; Ziegler, David; Dun, Matthew
Abstract: BACKGROUND: Diffuse Intrinsic Pontine Glioma (DIPG) is a devastating, incurable childhood brain cancer. 80% of patients harbour a genetic lesion to Histone-H3 with a substitution of lysine 27 for a methionine (K27M) ( H3F3A /H3.3 and HIST1H3B /H3.1) which results in the loss of methylation, interfering with chromatin function, activating oncogenic transcription. Unfortunately, H3 mutations are not directly targetable. RTK-RAS-PI3K pathway alterations occur in more than half of these patients (69%), and may represent a more promising therapeutic target. However, PI3K inhibitors have been notoriously ineffective due to their inability to cross the blood-brain-barrier (BBB). Targeting downstream components of the PI3K-AKT-mTOR signalling axis is a promising paradigm for PI3K mutant patients. This project aims to overcome the limitations of targeting downstream effectors of the PI3K pathway by utilising a novel PIK3CA specific, BBB permeable inhibitor, GDC-0084, currently in clinical trials for Glioblastoma (GBM) and DIPG. METHODS: Utilising DIPG patient derived (PDX) cells harboringH3K27M mutations (n=6), and +/- PI3K mutations, we examined the in-vitro efficacy of GDC-0084 on cell proliferation compared to Rapamycin. Phosphoproteomic profiling is currently underway investigating the role GDC-0084 has on inhibition of downstream oncogenic signalling pathways. Assessment of efficacy in a PDX in-vivo model is currently in progress. RESULTS: GDC-0084 significantly reduced the growth of all DIPG cell lines regardless of whether they harboredPI3K mutations (p=<0.001), and were significantly more cytotoxic than the mTORC1 inhibitor Rapamycin (p=<0.01). DIPG cell lines were also more sensitive to PI3K inhibition by GDC-0084 compared to GBM cell lines (n=4, p=<0.001) highlighting the therapeutic potential of GDC-0084 for the treatment of DIPG. Combining GDC-0084 and Vandetanib in DIPG revealed synergistic effects. CONCLUSIONS: While there are currently no therapeutics effective against the transcriptional programs elicited by H3 mutations, these studies re-ignite the potential for PI3K inhibition as a therapeutic target for DIPG.